Sensitivity and tolerance of different annual crops to different levels of banana shade and dry season weather - Blomme, Guy; Ntamwira, Jules Bagula; Kearsley, Elizabeth; Bahati, Liliane; Amini, Daniel; Safari, Nancy; Ocimati, Walter (Frontiers Media, 2020)
Intercropping in small-holder production systems in East and Central Africa is very common and offers potential for significant yield and environmental benefits. However, the reduced light availability under banana canopies constrains the success of the intercrop in banana systems. Determining a balance between the optimal spacing/densities of banana plants with optimized intercrop selection based on their sensitivity and tolerance to shade is imperative. This study, through extensive field experiments performed in South Kivu, DR Congo investigated the resilience of a wide range of food and forage crops to varying banana shade levels. The same crop species grown as monocrops served as controls. Quantitative yield assessments showed yam, sweet potato, ginger and forage grasses to have a good potential to grow under moderately dense to dense banana fields. Taro, soybean, mucuna, chili, eggplant, and Crotalaria sp. performed well in sparsely spaced banana fields with moderate shading. Cassava and soybean showed limited tolerance to shade. Intercropping in banana systems is also generally confined to the rainy seasons due to the high sensitivity of most annual intercrops to long dry weather in the dry season months. We also thus assessed the sensitivity of chickpea and mucuna to the long dry weather of the dry seasons and found them to have great potential for extending farming production into the dry season. Overall, we show that careful selection and allocation of crops with varying sensitivity to various banana shade levels and dry season weather can potentially increase whole field productivity.